Morphometric analysis of a drainage basin with Oyu Tolgoi Cu-Au deposit, South Mongolia - Khukhuudei, Ulambadrakh (Scientific transaction of the National University of Mongolia. Physics, 2022)
Morphometric analysis represent relatively simple approaches to describe basin processes and to compare basin characteristics. This study allows the description of the physical changes in a drainage system over time in response to natural disturbances or human impacts. The drainage characteristics for Oyu Tolgoi deposit studied to describe and evaluate their hydrological characteristics by analyzing topographical maps and satellite images. Scholars would attend to morphometric study, regarding with Mongolia hasn’t been publishing papers for this subject since the end of 1980’s.